An Etymology of Afrikaans ghoen (‘a shooting-marble’) - Bergerson, Jeremy (Werkwinkel, 2019)
The Afrikaans word ghoen (‘a shooting-marble’) arose in a setting wherein Malay, Khoekhoe, and Dutch were spoken and in which children played and shared vocabulary. Given the similarity of meaning and sound shape among Malay gundu (‘a marble’), Khoekhoe !gon (‘to throw something on the ground’), and dialectal Dutch koen (‘a shooting-marble’), I propose that these semantically and phonetically similar etyma merged into the word ghoen through a process, here referred to as lexical syncretism, which has been remarked on by other scholars of language history and contact.